A criaç\~ao do Mercosul contribuiu para aumentar a intensidade tecnológica das exportaç\~oes da regi\~ao? - Marcelo José Braga Nonnenberg; Allan Mesentier (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– The paper asks whether the creation of Mercosul has resulted in any increase in the exports technology intensity of its member countries and whether it has resulted in an increase of its exports. For that purpose, the authors have utilized an indicator of export technology intensity. The first result was that the technology intensity of intra-regional exports increased much faster than to the rest of the world. Second, the increase of technology intensity of intra-regional exports was strongly correlated to the bigger degree of concentration, which was the result of the growth of the automotive supply chain.
Keywords: F15; O33; 330